The Key Attributes of Effective Resolution Regimes for Financial Institutions : Progress to Date and Next Steps. (Policy Papers; Policy Paper, 2012)
The financial crisis underscored the need to develop an effective international framework to resolve cross-border financial institutions and groups. The development of such a framework has been a priority for the international community. Many important milestones have been achieved-most notably the adoption by the Financial Stability Board (FSB) of the Key Attributes of Effective Resolution Regimes for Financial Institutions (the Key Attributes) which is emerging as a new (nonbinding) international standard. Fund staff have been heavily involved in their development. The Key Attributes specify essential features that should be part of the resolution framework at both the national and international levels, with the key objective of making resolution feasible without severe systemic disruption and without exposing taxpayers to loss. These features include a comprehensive 'toolkit' of resolution powers for national authorities, including powers to: (i) assume control of a financial institution from existing managers and owners; (ii) effect a resolution of the troubled institution through the sale or merger of the entity, the transfer of assets and liabilities of the institution to third parties, or through unilateral debt restructuring or 'bail-in'; and (iii) support the resolution through a temporary stay on the execution of early termination rights under financial contracts.